The Unique Ability of Fine Roots to Reduce Vegetated Coastal Dune Erosion During Wave Collision - Figlus, Jens; Sigren, Jacob M.; Feagin, Rusty A.; Armitage, Anna R. (Frontiers in Built Environment, 2022)
Vegetated coastal sand dunes can be vital components of flood risk reduction schemes due to their ability to act as an erosive buffer during storm surge and wave attack. However, the effects of plant morphotypes on the wave-induced erosion process are hard to quantify, in part due to the complexity of the coupled hydrodynamic, morphodynamic, and biological processes involved. In this study the effects of four vegetation types on the dune erosion process under wave action was investigated in a wave flume experiment. Sand dune profiles containing real plant arrangements at different growth stages were exposed to irregular waves at water levels producing a collision regime to simulate storm impact. Stepwise multivariate statistical analysis was carried out to determine the relationship of above- and below-ground plant variables to the physical response. Plant variables included, among others, fine root biomass, coarse root biomass, above-ground surface area, stem rotational stiffness, and mycorrhizal colonization. Morphologic variables, among others, included eroded sediment volume, cross-shore area centroid shift, and scarp retreat rate. Results showed that vegetation was able to reduce erosion during a collision regime by up to 37%. Although this reduction was found to be related to both above- and belowground plant structures and their effect on hydrodynamic processes, it was primarily accounted for by the presence of fine root biomass. Fine roots increased the shear strength of the sediment and thus lowered erosional volumes and scarp retreat rates. For each additional 100 mg/L of fine roots (dry) added to the sediment, the erosional volume was reduced by 6.6% and the scarp retreat rate was slowed by 4.6%. Coarse roots and plant-mediated mychorrizal colonization did not significantly alter these outcomes, nor did the apparent enhancement of wave reflection caused by the fine roots. In summary, fine roots provided a unique ability to bind sediment leading to reduced dune erosion.